The experience of intersubjectivity in feminist research: methodological perspectives - Neiva Furlin (Educação e Pesquisa, 2015)
This article aims to contribute to the studies of research methodology. To this end, we seek to reflect on the experience of an engaged research that clearly shows the influence of the researcher’s existential trajectory on the choice of her object of study, as well as the methodological perspectives that favor the experience of intersubjectivity in the production of knowledge. The ultimate goal is to show that scientific research can be conducted based on a methodological paradigm that breaks with the subject-object dichotomy. As a reference to this discussion, we take an investigation that sought to understand how women constitute themselves as female subjects of theological knowledge and what power dynamics pervade the processes of entering and constructing a female faculty career in a place marked by hegemonic discourses and gender logics of a male social order. Therefore, we emphasize the hermeneutic perspective, as it allows to capture the meanings that female professors assign to their actions and experiences in the universe of theological knowledge. Hermeneutics as a research methodology favor the production of knowledge that is not intended as universal, but rather situated, subjective, and open to new interpretation perspectives. Such characteristics are central in the feminist epistemologies that seek to demystify the pure objectivity and universality of knowledge, showing that the subjects of knowledge are always immersed in a certain situation, position, and circumstance, and that, therefore, no knowledge is produced from nowhere.